Preparation and performance optimization of bromine-based perovskite quantum dot light-emitting diodes - CHEN Jiamin; CUI Xiangqian; HU Lufeng; YE Zhixiang; WANG Ning; LI Bobo; QIU Mingxia (Shenzhen Daxue xuebao. Ligong ban)
In order to investigate the effect of the thickness of the perovskite quantum dots light-emitting layer on the electro-optical conversion efficiency of perovskite quantum dot light-emitting diodes (PeLEDs), the cesium lead bromide (CsPbBr3) perovskite quantum dots were synthesized by ligand assisted reprecipitation (LARP) at room temperature, and the green PeLEDs with good stability were prepared. By comparing the luminous efficiency of CsPbBr3 PeLEDs with the different thicknesses of light-emitting layer, we obtained that the optimal film thickness of the quantum dot light-emitting layer is 43.2 nm, but the external quantum efficiency (EQE) of CsPbBr3 PeLEDs is very low. To improve the electro-optical conversion efficiency of the device, FASn0.3Pb0.7Br3 instead of CsPbBr3 quantum dots are used as the light-emitting layer, and the four different hole transport layers, such as polyvinylcarbazole (PVK), poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-butylphenyl) (TFB), poly[N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)-benzi (Poly-TPD) and poly[bis(4-phenyl)(2,4,6-triMethylphenyl)aMine] (PTAA), are selected to investigate the effects of different hole transport layers on the photoelectric properties of PeLEDs. The photoluminescence spectra and electrical performance test results show that when the hole transport layer is TFB, FASn0.3Pb0.7Br3 PeLED has a high hole mobility, and the EQE can reach up to 4.2%. The experimental results show that TFB is a suitable material for the hole transport layer of FASn0.3Pb0.7Br3 PeLED.